The Teacher in a Post-Conflict Context: A Sociological Understanding of Peace Education - Tamar Shinjiashvili; Lia Akhaladze (Соціологічні студії)
The article explores the sociological role of teachers in post-conflict contexts, with a particular focus on Georgia, a country shaped by ethnic conflicts and large-scale internal displacement. Drawing upon peace education theories and qualitative research methods, the paper analyzes how teachers act as agents of reconciliation, social cohesion, and transformation in societies deeply affected by trauma and conflict. Integrating theoretical contributions from Johan Galtung, Paulo Freire, and Betty Reardon, the study highlights how education can become a mechanism for fostering dialogue, critical thinking, and inclusive narratives. Empirical evidence is drawn from interviews with Georgian teachers working in internally displaced and ethnically diverse regions such as Shida Kartli, Samegrelo, and Marneuli. The findings reveal that teachers act not only as knowledge transmitters but also as agents of empathy, critical reflection, and intercultural dialogue. Despite limited institutional support and curriculum gaps, many teachers engage in informal peace pedagogy, navigating issues of trauma, historical narratives, and trust. The study underscores the necessity of trauma-informed teaching approaches, inclusive textbooks, and coherent peace-oriented education policies. It concludes that in the absence of systemic support, teachers’ agency remains vital for building a culture of peace. The Georgian case illustrates that peace education is not just a theoretical construct but an urgent pedagogical and sociopolitical response to ongoing post-conflict challenges.